Associations between tumor necrosis factor alpha gene -238 G/A and -308 G/A polymorphisms and the risk of pneumoconiosis: update of a meta-analysis. (November 2013) - Yin, Yan-Wei; Wu, Zhao-Guo; Sun, Qian-Qian; Hu, Ai-Min; Wang, Qi; Liu, Hong-Li
Abstract Objectives: Tumor necrosis factor alpha (TNF-α) gene (-238 G/A [rs361525] and -308 G/A [rs1800629]) polymorphisms have been extensively studied in relation to various diseases, several epidemiologic studies have been performed to investigate the associations of TNF-α gene polymorphisms with pneumoconiosis; however, the results of these studies were not entirely consistent. In an effort to clarify earlier inconclusive results, we performed this meta-analysis of case–control genetic association studies. Methods: We identified eligible studies by searching the relevant databases, including PubMed, Embase, Web of Science, CBMdisc, CNKI, and Google Scholar, until February 15, 2013. Additionally, hand searching of the references of identified articles were performed. Heterogeneity and publication bias across studies were determined and the meta-analysis was performed by Stata 11.0. Results: Fourteen articles involving 20 studies were included in the final meta-analysis, covering a total of 1935 pneumoconiosis cases and 3753 controls. The results showed evidence for significant association between TNF-α gene -308 G/A polymorphism and pneumoconiosis risk, suggesting that TNF-α gene -308 A allele may be a risk factor for pneumoconiosis (for A allele vs. G allele: OR = 1.41, 95% CI = 1.10–1.81, p = 0.01; for A/A + G/A vs. G/G: OR = 1.52, 95% CI = 1.21–1.91, p < 0.01). For TNF-α gene -238 G/A polymorphism, no significant association was found between this genetic variation and pneumoconiosis risk. Conclusions: This meta-analysis indicates that TNF-α gene -308 G/A polymorphism is associated with an increased pneumoconiosis risk.